Vessel morphology variation and ecoanatomical properties of anjily (Artocarpus hirsutus Lam.) wood grown in different agro-climatic zones of Thrissur, Kerala - Sahoo, Swagatika; Anoop, E.V.; Vidyasagaran, K.; Kunhamu, T.K.; Santhoshkumar, A.V. (Journal of Tropical Agriculture, 2017)
Vessel morphological parameters viz., vessel frequency, vessel diameter, vessel area and vessel length of anjily wood collected from trees grown in three agro-climatic zones of Thrissur district, Kerala were studied. Three girth classes were selected from each zone. Three trees representing each girth class were then chosen for collection of wood samples. Significant variation was found only among agro-climatic zones for vessel length and not between girth classes within zones. Vessel area, vessel diameter and vessel frequency did not show any significant variation between three zones as well as between girth classes. Ecoanatomical properties like vulnerability and vessel mesomorphy were also calculated. Vulnerability showed significant difference between the three zones. Vessel mesomorphy values of anjily wood indicated that the species is mesic in nature.